2003
DOI: 10.1074/jbc.m308259200
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Studies of the O-specific Polysaccharide of Shigella flexneri 5a and of Four Related Synthetic Pentasaccharide Fragments Using NMR and Molecular Modeling

Abstract: As part of a program for the development of synthetic vaccines against the pathogen Shigella flexneri, we used a combination of NMR and molecular modeling methods to study the conformations of the O-specific polysaccharide (O-SP) of S. flexneri 5a and of four related synthetic pentasaccharide fragments. The NMR study, based on the analysis of 1 H and 13 C chemical shifts, the evaluation of inter-residue distances, and the measurement of oneand three-bond heteronuclear coupling constants, showed that the confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 54 publications
11
52
0
Order By: Relevance
“…S4), showing that both observed AB conformations in the two serotypes are favorable. Similarly, the ␣-D-Glcp(E)-(1-Ͼ3)-␣-L-Rhap(B) linkage of the 5a serotype is not sterically compatible with the Y serotype structure, as has been previously noted (24). The pattern of serotype glucosylation can therefore impose constraints on the structure of extended O-Ag chains.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…S4), showing that both observed AB conformations in the two serotypes are favorable. Similarly, the ␣-D-Glcp(E)-(1-Ͼ3)-␣-L-Rhap(B) linkage of the 5a serotype is not sterically compatible with the Y serotype structure, as has been previously noted (24). The pattern of serotype glucosylation can therefore impose constraints on the structure of extended O-Ag chains.…”
Section: Discussionmentioning
confidence: 79%
“…The model polysaccharide chain thus obtained is a right-handed helix of pitch Ϸ23 Å, diameter Ϸ15 Å, and nearly three RUs per turn. Interestingly, the helix has similar parameters to the model proposed for serotype 5a O-Ag, which was based on NMR data and modeling studies (24). But unlike the serotype 5a model, where Glc(E) protrudes outwards perpendicular to the helical axis in a solvent-exposed orientation, Glc(E) in the serotype 2a is folded under the backbone at approximately the same radial distance from the helical axis as the residues ABCD.…”
Section: Implications For O-antigen Structure In Lpsmentioning
confidence: 78%
“…In addition, inter-residue 1 H-1 H distances were also calculated from a trROESY spectrum obtained with a mixing time of 400 ms to take spin diffusion into account, if any. Comparison of these distances with those measured for unbound DA(E)BC-OMe (33) suggested that the pentasaccharide conformation was not significantly modified upon binding to the mIgAs (Table 5).…”
Section: Peptidesmentioning
confidence: 99%
“…Clustering of solutions was done by root mean square fitting (Ͻ1 Å). The best solution of each cluster was used to propagate the helices to 20 residues while keeping the conformations determined previously (33). Twenty different conformers of the p100c peptide were also docked in the mIgA I3 Fab-binding site using the rigid body approach of the Autodock3 program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation